The Effect of Interactive Multimedia on Critical Thinking in Social Studies Learning for Grade V in Elementary Schools - Irmawati, Leni; Fitra Raharja, Hawwin (Prodi PGSD Fakultas Ilmu Pendidikan (FIP) Universitas Hasyim Asy'ari (Unhasy) Tebuireng Jombang, 2021)
Education is the most important factor in determining one's future. With education, it can help humans to think about following developments in the modern era as it is today. It is the same as helping students think critically. As happened at SDN Kaliwungu 2 Jombang, teaching and learning activities that do not use media make students feel bored when studying and find it difficult to improve students' critical thinking. The purpose of this study was to determine the effect of interactive multimedia on students' critical thinking on the material of human interaction with the environment and its effect on social development in fifth grade elementary school. This type of research is a quantitative experiment through a one group pre test post test design. The population of the study were all students of class V SDN Kaliwungu 2 Jombang, which amounted to 20 students, according to the results of data analysis showing that the lowest pretest score was 32 and the highest score was 88 with an average of 61.20 while the lowest posttest score was 56 and the highest score was 92 with an average of 75.80, based on calculations showed an increase after learning to use interactive multimedia. These results indicate that there is an influence on the creativity of critical thinking in social studies learning in class V at the elementary school level.